Ikea - Hisrich, Robert D.; Kearney, Claudine ([London] : SAGE, 2016)
This case reviews the entrepreneurial example of IKEA and the expansion of the company. It examines the profile of the company's founder, the innovative Ingvar Kamprad, and his early beginnings in his hometown in Sweden.
Originally Published in: Hisrich, R. D., & Kearney, C. (2013). Scenario: IKEA. In Managing innovation and entrepreneurship (pp. 106-109). Los Angeles: SAGE Publications, Inc. ISBN: 9781452241357.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Ikea (Firm); Entrepreneurship -- Case studies